Involvement of poly(ADP-ribose) polymerase-1 in development of spinal cord injury in Chinese individuals: a Chinese clinical study - Meng Q; Yang G; Li R; Nie J; Zhou W; Yu H; Chen B; Jiang L; Shang J (Dove Medical Press, 2017)
Qing-Tao Meng,* Guang Yang,* Ren-Bo Li, Jing-Xin Nie, Wei Zhou, Hong-De Yu, Bo Chen, Li Jiang, Jing-Bo Shang Department of Spine Surgery, The Third People’s Hospital of Dalian, Dalian, People’s Republic of China *These authors contributed equally to this work Objective: We aimed to evaluate whether the polymorphism of poly(ADP-ribose) polymerase-1 (PARP-1) is involved as potential risk factor in the development of spinal cord injury (SCI) among Chinese individuals.Patients and methods: Patients with a confirmed diagnosis of SCI (other than traumatic injury) and healthy individuals with no clinical symptoms of SCI were enrolled at Spinal Cord Injury Care Center, The Third People’s Hospital of Dalian, China. Genetic polymorphisms were studied in plasma samples by polymerase chain reaction-restriction fragment length polymorphism assay.Results: A total of 130 Chinese patients with SCI and 130 healthy Chinese individuals were included. We found that patients with the GG genotype (odds ratio [OR]: 4.09, 95% confidence interval [CI] 2.42–6.90, P<0.001) and carriers of the G allele (OR 3.96, 95% CI 2.33–6.74, P<0.0001) were at high risk of developing SCI. A del/ins polymorphism of the NF-κB1 gene (OR 3.32, 95% CI 1.96–5.61, P<0.001) was also found to be associated with SCI.Conclusion: Our study suggests that PARP-1 polymorphisms are involved in the development of SCI in Chinese individuals. Thus, PARP-1 polymorphisms can be considered as one of the potential risk factors for developing SCI. Keywords: spinal cord injury, poly(ADP-ribose) polymerase-1, polymorphism